A gestão da informação e o processo decisório no setor energético: aplicação do método AHP na mensuração de critérios e alternativas - Rogerio Amaral Bonatti (2015)
This research has the purpose to identify the information flow for decision-making processes at energy sector. The development of a model provides the choice of a method for the measurement criteria and alternatives that relate to a problem to be solved or an established goal. The questions about the Information and Knowledge Management at Strategic Planning and the informational survey contributed to the elaboration of this information model of reference on the energy sector. The study on decision-making processes was directed to the energy sector and involves more precisely, projects of power generation from alternative renewable sources. The definition of a problem allows for the possibility of applying advanced analysis method Analytic Hierarchy Process. The choice of this method has made from the literature researched and recent work in different areas of knowledge that allude to knowledge management and the importance of information in decision making processes. The flexibility and simplicity of drawing up the problem of hierarchy are favorable to the adoption of this method. Its application was performed on a situation originally from analysis results obtained through questionnaires and with the help of consultants and industry experts who are involved in the strategic area of their respective organizations. The Analytic Hierarchy Process uses the aggregation of intangible variables and among some advanced methods studied decision analysis, proved to be good applicability. The application of this method highlights the need for a computational resource for conducting lot of comparisons between the preferences of managers and the subjective aspect of the trials. The involvement of the persons responsible for strategic decisions is a key factor for the correct use of this advanced with analysis method. It was demonstrated during the research that the practices of information management and knowledge provide the correct conversion of informational input in the form of criteria and alternatives considered, which provides the core elements of the process of hierarchical analysis.